DESCRIPTION OF TRICHURIS SP. RECOVERED FROM A FREE-RANGE GAUR (BOS GAURUS) - S.T. Bino Sundar; K. Rajeshkumar; M. Aravind; K. Jeeva; B. Nishanth; P.N. Richard Jagatheesan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The occurrence of Trichuris sp. nematodes in the caecum and colon of a free-ranging female gaur (Bos gaurus) observed during necropsy is reported. The body condition of the animal was thin with appreciable muscle wasting, sunken eye balls, rough hair coat, enlarged lymph nodes and pale mucous membrane. On necropsy, worms were found adhering to the mucosa of the caecum and colon. The worms were collected in 10% formalin, processed and identified as Trichuris sp. The worms were white in colour with whip-like anterior end, males were shorter than females. A total of 265 worms were recovered out of which 80 were male worms and 185 were female worms. The adult males were 30-55 mm long and 0.2-0.6 mm in width with a slender filiform anterior end comprising and a coiled posterior end. The adult females were 60-70 mm long and 0.3- 0.6 mm in width with a straight posterior end. It is however not probable that this infection could be one of the factors causing death of the animal.